2017
DOI: 10.1002/fuce.201600212
|View full text |Cite
|
Sign up to set email alerts
|

Zincating Effect on Corrosion Resistance of Electroless Ni‐P Coating on Aluminum Alloy 6061

Abstract: Aluminum and its alloys represent a promising alternative as bipolar plates in proton exchange membrane fuel cell (PEMFC) systems. However, to improve the corrosion resistance they are commonly coated, and electroless Ni‐P offers great advantages. The effect of multiple zincating process on the corrosion behavior of electroless Ni‐P coatings on AA6061 was investigated. Results of morphological characterization and compositional analysis of the electroless Ni‐P coatings showed that as the number of zincating st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A negative effect of copper on corrosion properties was also observed for pre-galvanized aluminum alloys, Ni-Co-P [46] and Ni-P coated aluminum alloys [160], where higher phosphorus content is desirable in order to achieve higher amorphous structure and better corrosion properties. In addition, repeated zinc plating makes it possible to achieve a better morphology of the N-P coating on galvanized aluminum 6061 and a lower corrosion rate of 4.4 µA•cm −2 , but the resistance properties were not measured [161]. Ni-P-Cr was prepared on AA 7075-T6 and consisted of 20 µm Ni-P interlayer with 10 µm of electroplated Cr.…”
Section: Aluminiummentioning
confidence: 99%
“…A negative effect of copper on corrosion properties was also observed for pre-galvanized aluminum alloys, Ni-Co-P [46] and Ni-P coated aluminum alloys [160], where higher phosphorus content is desirable in order to achieve higher amorphous structure and better corrosion properties. In addition, repeated zinc plating makes it possible to achieve a better morphology of the N-P coating on galvanized aluminum 6061 and a lower corrosion rate of 4.4 µA•cm −2 , but the resistance properties were not measured [161]. Ni-P-Cr was prepared on AA 7075-T6 and consisted of 20 µm Ni-P interlayer with 10 µm of electroplated Cr.…”
Section: Aluminiummentioning
confidence: 99%
“…Typically, the corrosion resistance of the EL-plated components depends on the degree of crystallinity, P content, phase change, coating thickness, porosity on the surface, size, and orientation of grains [ 19 , 20 , 21 ]. As per a study by Gutierrez et al, the corrosion resistance of the Ni-P EL-coated component depends upon the P content, the extent of internal stress, and the amorphous state [ 22 ]. The performance evaluation of Ni-P coated surfaces has been conducted in the context of the factors mentioned above in several studies [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various surface modification techniques for the preparation of alloy coatings have been implemented as common methods such as physical vapor deposition (Cui et al , 2021; Vannozzi et al , 2018), electrodeposition (Zhang and Zhang, 2019; Mahalingam and Bera, 2020; Ma et al , 2020) and electroless plating (Wang et al , 2020; Shi et al , 2017). Among all technologies, electroless plating of Ni-P alloy coatings was preferred because of the low cost and unique preparation advantages (Shu et al , 2019; Li et al , 2019; Gutierrez et al , 2017). Numerous transition metals for example Mn (Jiang et al , 2019), Fe (Yang et al , 2019), Cu (Wang et al , 2020; Chen et al , 2017), Mo (Rosas-Laverde et al , 2020), Co (Sarika et al , 2021) and W (Tian et al , 2021; de Oliveira et al , 2018) have been reported in many publications, which have been used to broaden the performance of electroless Ni-P coatings.…”
Section: Introductionmentioning
confidence: 99%